Defining Iran : politics of resistance - Holliday, Shabnam J. (Ashgate Pub., 2011)
This book examines what it means to be Iranian and how Iranian national identity is constructed; how Islam, Iran's pre-Islamic culture, and relations with the West are dealt with and determining what is authentic and legitimate.